2019
DOI: 10.1080/21679169.2019.1636133
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ experiences of direct access for clients with musculoskeletal pain and dysfunction: a qualitative study

Abstract: AimsThis study focused on direct access-practice in physiotherapy by surveying the experiences of physiotherapists who work in direct access with clients having musculoskeletal pain or dysfunction. MethodsThis was a descriptive, mixed method study where data were collected from questionnaires given to 34 physiotherapists, 18 of them being in direct access for 6 years and 16 for 6 months. There were 15 structured questions and 3 open-ended ones. The answers were analysed with quantitative and qualitative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Comparing the Findings from Theme 1 with Previous Literature "Opportunity to advance career" was the most prevalent subtheme to emerge under the overarching theme 1: "Decision to choose a career path as a musculoskeletal first contact physiotherapist". A qualitative study of MSK FCPs in two large municipal healthcare organizations in Finland also indicated that FCP was seen as a career advancement (Karvonen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the Findings from Theme 1 with Previous Literature "Opportunity to advance career" was the most prevalent subtheme to emerge under the overarching theme 1: "Decision to choose a career path as a musculoskeletal first contact physiotherapist". A qualitative study of MSK FCPs in two large municipal healthcare organizations in Finland also indicated that FCP was seen as a career advancement (Karvonen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The training also included the identification of signs of serious diseases, assessment of the need for consultation with a doctor, on the basis of symptomatic and findings of examination, and assessment of psychosocial stress factors, e.g. through a written questionnaire [4,5]. When interviewing the clients, it was also instructed to recognize the clients` life situation and its effects on experiencing pain and the suitability of the instructions, utilizing the various elements of the international functional classification (ICF) from general health to environmental and personality factors (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…MSDs can be managed through the modern practice of referral to physiotherapy at the primary level of health care; the so-called direct access, which refers to a term used for patients seeking the services of a physiotherapist without the recommendation of a third party or a health professional, usually a physician [5,[7][8][9][10][11]. Self-referral is an opportunity for clinical evaluation and physiotherapy advice plan aimed at disabling and preventing possible future dysfunction at an early stage [12] without a referral from a physician [13], usually a specialist, which is contrary to the current practice of the traditional referral model in Croatia. Evidence supports physiotherapeutic management and other specific conditions at the primary level rather than in acute hospitals, such as neurological conditions and women's health problems [14].…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapists at the primary level of health care contribute to addressing the rapidly growing needs of the population, which represent direct demands on the health system and are directly related to rising health care costs in Europe [14]. In Finland, the Netherlands, Norway, Sweden and the United Kingdom, the self-referral model or direct access to physiotherapy in primary care is standard, thoroughly evaluated and recommended by the National Institute for Health and Care Excellence [12,14]. European studies show that patient self-referral to physiotherapy has proven to be feasible, appropriate, clinically and financially effective, and supported by patients, physiotherapists and family physicians [15], who are considered "gatekeepers" at the primary level of health care.…”
Section: Introductionmentioning
confidence: 99%